Aizuchi in Japanese Language Online Class in Medan: Lecturer-Student Interaction - Mhd. Pujiono; Abdul Gapur; Taulia Taulia (Faculty of Humanities, Universitas Jenderal Soedirman, 2022)
Aizuchi is more frequently used in modern Japanese conversation than any other language. As a result, proper aizuchi usage is a significant indicator of Japanese conversational ability. In recent years, online classes are a state of learning that must be implemented due to the pandemic that is sweeping the world. This research examines the application of the frequency and form of aizuchi in student and lecturer interactions in online classrooms. Given the increasing importance of distance communication skills in foreign language learning in the future, this is an attempt to communicate the cultural context of indigenous learners in a global environment. Additionally, this type of research on distance communication between foreign language learners makes critical recommendations for the future facilitation of distance language learning. This research is qualitative research with a descriptive method. The data is aizuchi sourced from student interaction with lecturers in virtual classes at the Japanese department, Universitas Sumatera Utara and Universitas Harapan Medan. Data collection uses the record and note method. Interactive data analysis was used in analyzing the data. The results indicate that students in Japanese online classes rarely use aizuchi. The forms of aizuchi used by students are tandokukei (singular) and kurikaeshikei (singular repetition). In conclusion, students use aizuchi very limitedly, which does not help keep communication smooth and ultimately results in a tendency to get stuck or misunderstood in online class interactions.